Adequando mulheres produzindo "vítimas": uma análise sobre o discurso do Esquadrão da Moda - Pedro, Ana Carolina de Souza (2018)
This dissertation aims to discuss the moral pedagogy that focuses on the female body, taking as empirical object the reality show "Esquadrão da Moda", transmitted weekly by SBT. As basic methodological procedures, interviews with participants, friends and/or family members and professionals of the program team, as well as a content analysis of the episodes exhibited in the period from 2012 to 2016. We sought to select those in which the themes related to the main objective of the research: those that are indicated by women to dress sensuously, considering their association with the image of "piriguete" and, sometimes, with that of the call-girl, which most critical way involve control over body exposure and the perception of fashion as a set of codes and rules that dictate "good taste".